The Effect of Milkfish Bone Meal (Chanos chanos) Addition and Sodium Bicarbonate (NaHCO3) Concentration on the Physicochemical and Organoleptic Characteristics of Tortilla Chips - Bintang Safir Kelana, Mahatma; Sarofa, Ulya; Yulistiani, Ratna (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2024)
Tortillas are a corn-based snack, yellow, and have a thin shape and crunchy texture. The addition of fish bone meal can increase calcium levels but also decrease the texture of the tortilla. The addition of sodium bicarbonate aims to improve the texture by increasing the swelling power and crispness of the product. This research aims to determine the effect of the substitution of milkfish bone meal with the addition of sodium bicarbonate on the physicochemical and organoleptic characteristics of tortilla chips. This study used a Completely Randomized Design (CRD) with two factors and two replications, factor I was the concentration of milkfish bone meal (10%, 15%, and 20%) and factor II was the concentration of sodium bicarbonate (0.25%, 0.50 %, and 0.75%). The data obtained were analyzed using ANOVA and continued with the Duncan Multiple Range Test (DMRT) at the 5% level. The results of the research show that there is a real interaction with ash content, protein content, fat content, and calcium content. The research results of the best treatment based on physicochemical parameters were tortilla chips with the addition of fish bone meal 10% and a sodium bicarbonate concentration of 0.75%. This is the best-treated tortilla chip product with a water content value of 5.080%; ash content 2.995%; protein content 5.87%; fat content 5.380%; carbohydrates 82.521%, calcium 3.396%, expansion volume 19.912%; breaking power 278,350 gf; amylose 37.750%; and starch content 62.516%;